Route-Based Emissions Inventory and Energy Consumption of Passenger Vehicles: Case of Addis Ababa, Ethiopia - Amanuel Gebisa Aga; Girma Gebresenbet; Rajendiran Gopal; Ramesh Babu Nallamothu (Innovation and Green Development)
Emission inventories play a crucial role in identifying the primary sources of atmospheric pollution. In urban environments, including Addis Ababa, elevated concentrations of vehicle emissions pose significant environmental risks. Consequently, measuring vehicle emissions becomes imperative for estimating the impact of passenger vehicles on urban air quality. In 2022, a drive cycle specific to Addis Ababa was developed for the first time; however, it was not utilized for determining both fuel consumption and vehicle emissions. Previous studies on emission inventories primarily focused on vehicle classification, neglecting variations in emissions on different types of roads. This study introduces routes-based emissions inventories and fuel consumption estimates for passenger cars based on the Addis Ababa drive cycle and the Worldwide Harmonized Light Vehicles Test Cycle. To validate the model, an experimental chassis dynamometer setup was employed. The findings of this study revealed that driving in the congested urban areas of Addis Ababa contributes to 56.25 ​% carbon monoxide, 37.28 ​% carbon dioxide, 38.19 ​% nitrogen oxides, 58.25 ​% volatile organic compound, 29 ​% particulate matter emissions, along with 37.29 ​% fuel consumption. Furthermore, congested urban and rural areas in Addis Ababa account for 60 ​%–73 ​% of all emissions and fuel consumption from passenger vehicles. The Addis Ababa city administration shall adopt cleaner technologies, improve public transportation access, and implement stricter emissions standards to mitigate vehicular pollution in the city.